Community Views About Zakat on Cryptocurrencies - Nor Paizin, Muhsin (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2021)
The cryptocurrency industry has exploded, with an increasing number of individuals investing in digital assets — even Malaysians who adhere to Shariah financial norms. The surge in Islamic faith members' involvement in cryptocurrencies such as Bitcoin and Ethereum has given birth to Zakat payments. Zakat is the third pillar of Islam, and it compels Muslims to make charitable contributions if they have sufficient means. The major considerations to explore are whether zakat is required on cryptocurrency investments and how the community sees zakat on cryptocurrencies. As a result, this paper will investigate the prospect of cryptocurrencies as a digital assets being a new source of revenue for zakat from an Islamic perspective by acquiring appropriate rulings (fatwas) and then investigating community attitudes on zakat on cryptocurrency.